The Influence of Interactive Learning Media Usage on Student Learning Motivation in Islamic Religious Education at Elementary Schools - Saputra, Dedi (Jurnal Ar Ro'is Mandalika (Armada), 2023)
In the realm of elementary education, particularly in the context of Islamic Religious Education (IRE), the integration of interactive learning media has emerged as a promising strategy to enhance student engagement and motivation. This study investigates the impact of utilizing interactive learning media on student learning motivation in IRE at the elementary level. Employing a qualitative approach, this research conducts an extensive literature review and library research to explore existing studies, theories, and models related to interactive learning media and student motivation. The findings reveal that the integration of interactive learning media in IRE instruction positively influences student learning motivation. Interactive media, such as educational games, multimedia presentations, and virtual simulations, offer dynamic and engaging learning experiences, stimulating students' interest and intrinsic motivation. Furthermore, interactive learning environments provide opportunities for active participation, collaboration, and personalized learning, catering to diverse learning styles and preferences among elementary students. The utilization of interactive media fosters a sense of autonomy, competence, and relatedness, which are key components of self-determination theory and motivational frameworks. This heightened motivation leads to increased attentiveness, enthusiasm, and persistence in learning IRE topics. The implications of these findings underscore the importance of integrating interactive learning media into IRE pedagogy to cultivate a supportive and motivating learning environment for elementary students. This research contributes to the existing literature by highlighting the significant role of interactive media in promoting student motivation and engagement in religious education contexts.